Participating in food waste transitions: exploring surplus food redistribution in Singapore through the ecologies of participation framework. Issue 1 (2nd January 2021) - Rut, Monika; Davies, Anna R.; Ng, Huiying
ABSTRACT: Food waste is a global societal meta-challenge requiring a sustainability transition involving everyone, including publics. However, to date, much transitions research has been silent on the role of public participation and overly narrow in its geographical reach. In response, this paper examines whether the ecologies of participation (EOP) approach provides a conceptual framing for understanding the role of publics within food waste transitions in Singapore. First the specificities of Singapore's socio-political context and its food waste management system is reviewed, before discussing dominant, diverse and emergent forms of public engagement with food waste issues. This is followed by in-depth consideration of how participation is being orchestrated by two surplus food redistribution initiatives. Our analysis finds the EOP beneficial in its elevation of participation within the transitions field. It also provides a useful means to deconstruct elements that comprise participation practices and discuss culture-specific motivations, organisational realities and visceral experiences.